Social media, opposition political parties and democratic governance in authoritarianist countries in Africa - Tametong, Steve (University of the Witwatersrand, Johannesburg, 2023)
The objective of this paper is to demonstrate that social media has redefined the modalities of political communication and facilitated the organisation of collective mobilisation by opposition political parties in authoritarian regimes in Africa. Taking Cameroon and Chad as case studies, the paper shows that social networks (Facebook) have overtaken traditional communication tools and enabled opposition political parties during the electoral period to mobilise voters, encourage their participation in the vote, raise funds for the electoral campaign and ensure the transparency of the electoral system. Outside of election periods, social media allows opposition political parties to build and maintain a permanent relationship with grassroots activists. The study demonstrates that social media constitutes a threat to autocratic regimes and the way in which these regimes multiply strategies to limit their impact in the qualitative transformation of society. Using a qualitative approach and the theoretical framework of new forms of political mobilisation, the analysis is based on empirical data collected from interviews, questionnaires, observation and digital traces of the presence of four opposition political parties in Cameroon and Chad. Finally, this study recommends that opposition political parties take advantage of social media to build real democracy governance in Africa in the digital age.
Keywords: African Governance; Digital Age; Authoritarianism; Democratic governance; Mobilisation; Opposition political parties; Social media; SDG-9: Industry, innovation and infrastructure